Late prehistoric bone marrow extraction : a case study in western Wisconsin - Pfaffenroth, Jake (My University, 2009)
The Swennes Upper Garden Terrace site (47Lc333) in La Crosse County, Wisconsin has been the location of multiple excavations by the Mississippi Valley Archaeology Center at the University of Wisconsin-La Crosse since 1995. Of the many late prehistoric Oneota pit-features discovered at the site, Feature 30 was found to contain several hundred white-tailed deer (Odocoileus virginianus) bone fragments. These bones displayed characteristics indicating they had been systematically fractured in the production of "bone grease." Bone grease is obtained by boiling the fatty bone marrow out of the cancellous tissue of bones and is high in nutrients. Its production and use is documented ethnographically and archaeologically in various regions and climates. This paper examines the bone fragments from Feature 30 through quantitative analysis and the use of ethnographic, archaeological, and experimental literature, with the goal of interpreting the human processes resulting in their deposition within the feature.
Keywords: Oneota Indians (Great Plains) -- Wisconsin -- La Crosse County -- Antiquities; Bone marrow; White-tailed deer -- Wisconsin -- La Crosse County; Animal remains (Archaeology) -- Wisconsin -- La Crosse County